Point of view on the vaccination against COVID-19 in patients with autoimmune inflammatory rheumatic diseases - Victoria Furer; Christien Rondaan; Nancy Agmon‐Levin; Sander van Assen; Marc Bijl; Meliha C Kapetanovic; Annette de Thurah; Ulf Mueller‐Ladner; Daphna Paran; Karen Schreiber; Klaus Warnatz; Nico Wulffraat; et al. (2021)
In view of the COVID-19 pandemic, there is an unmet clinical need for the guidelines on vaccination of patients with autoimmune inflammatory rheumatic diseases (AIIRD). This position paper summarises the current data on COVID-19 infection in patients with AIIRD and development of vaccines against COVID-19, discusses the aspects of efficacy and safety of vaccination, and proposes preliminary considerations on vaccination against COVID-19 in patients with AIIRD, mainly based on the expert opinion and knowledge on the use of other vaccines in this population of patients.